The in situ stress field and microscale controlling factors in the Ordos Basin, central China. (November 2020) - Liu, Jingshou; Yang, Haimeng; Wu, Xiaofei; Liu, Yang
Abstract: To ensure the effectiveness of fracturing treatment and improve the production reserves of individual wells, it is important to accurately predict the in situ stress distribution to prevent the collapse of horizontal wells. From the perspective of reservoir development, under similar structural environments, microscopic factors, such as reservoir and petrophysical characteristics, are often the key factors that affect reservoir fracturing differences and drilling design in different well areas. Therefore, we need to understand the microscopic factors that affect the distribution of in situ stress. Here, we have determined the three-dimensional distribution of in situ stress in the Ordos Basin of China through the finite element numerical simulation method and revealed the influencing factors. By establishing a reservoir heterogeneity model and a geomechanical heterogeneity model and with the finite element method, the 3D distribution of reservoir physical parameters and in situ stress can be predicted, and the effects of the reservoir physical properties, fluid properties, rock acoustic velocity and mechanical properties on the in situ stress can be determined. The clay content is found to be negatively correlated with the horizontal stress difference (Δ σ ) and horizontal principal stress difference coefficient ( K h ). Rock density, porosity, and permeability have little effect on Δ σ and K h . Fluid properties affect the in situ stress magnitude. If the water saturation is greater than 60%, this parameter has a negative correlation with Δ σ and K h . Poisson's ratio has a weak effect on Δ σ but a significant negative correlation with K h .